Uma análise do desempenho dos fundos de investimento multimercados no Brasil - Lima, Urquiagga Holanda (2015)
This study aims to analyze the performance of multimarket investment funds, subtype balanced, in Brazil. Characterized by the active management model, multimarket investment funds have the policy to apply the resources of its shareholders in different asset classes, in order to get the best performance, considering the binomial risk and return. Based on a sample of 128 multimarket investment funds for the period January 2010 to December 2014, parametric and non parametric tests were applied, based on performance evaluation of classic models proposed by Treynor (1965), Sharpe (1966), Jensen (1968), Sortino (1994) and Modigliani and Modigliani (1997). The results show that for the period analyzed, the multimarket investment funds were able to overcome the major market benchmarks. It has also proven performance persistence for all analyzed frames, using parametric and non parametric tests. As the analyze about the relationship between the characteristics of investment funds and their performance, tha evidence that was found suggesting a positive relationship to the variable size, and a negative relationship to the variables age, administration fee and management foreign bank.